Overcoming The Challenges of Students’ Self-Efficacy: A Review That Leads to Solutions in Chemistry Learning - Simanjuntak, Yanni Irma Waty; Linda, Desma; Menno, Ayu Windy Malisa (Jurnal Pendidikan MIPA, 2025)
Self-efficacy is essential in the process of achieving learning goals. Individuals with higher self-efficacy tend to choose to work on difficult and challenging tasks. This study aims to explore the solutions for students’ self-efficacy challenges in chemistry learning. This study used a systematic literature review method. The Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA) approach was adopted for this review. The search was based on the keywords “self-efficacy”, “students”, “challenges”, “solutions”, and “chemistry learning” which resulted in articles using alternative terms to describe self-efficacy and specific interventions. A total of 13 research articles reviewed in this article were collected from databases such as SCOPUS, ERIC, and Google Scholar. The thematic analysis procedure was used to determine emerging themes. The six steps of thematic analysis are as follows: familiarization with the data, initial coding, search for topics, evaluation of themes, representation of themes and interpretation of results. The results of the review showed that there are several interventions that can improve students' self-efficacy in chemistry learning, including the use of game-based learning media, virtual learning media, and the application of certain models, strategies, and approaches such as problem-based learning (PBL), PBL-STEM, process oriented guided inquiry learning (POGIL), inquiry-based learning (IBL), SSI integration, metacognitive strategies, the implementation of efficacy-enhancing teaching, and also the use of core idea maps. Therefore, collaboration between educational institutions, schools and teachers is required in the implementation of this intervention. This collaboration will ensure a supportive environment, both inside and outside the classroom so that it has the potential to overcome students' self-efficacy challenges in chemistry learning.        Keywords: chemistry, learning, self-efficacy, solutions.